Barisan Modul Eksak dan Barisan Homomorfisma Modul Eksak - Yanita Yanita (Universitas Islam Bandung, 2008)
This article explained sequence exact of R-module and R-module homomorphism and their relation. Module is generalized of vector space V over field F. If M module over ring R, usually denoted M R-module. Module sequence is defined as homomorphism sequence from module to another module. R-Module sequence have exact property at a module, for example Mi, if kernel function from Mi to Mi+1 same with image function from Mi-1 to Mi. The set of all R-module homomorphisms from Mi to Mi+1 will be denoted HomR(Mi,Mi+1). HomR(Mi,Mi+1) is also module over ring which the same with Mi and Mi+1.